Test of the Aphrodisiac Effect of Ethanol Extract of Roots, Stems and Leaves of Packaged Plants (Smilax rotundifolia) on Male White Rats (Sprague Dawley) - Kiki Rizki Handayani; Ayu Wulandari (Journal of Tropical Pharmacy and Chemistry, 2021)
Developing countries use medicinal plants for aphrodisiac treatment, one of which is a pack plant (Smilax rotundifolia) which is commonly used to enlarge male genitalia in Papua Indonesia. Because these claims are not scientifically tested and proven, at this time This study aims to determine the effect of the ethanol extract of S. rotundifolia stem and leaf tubers on the parameters of sexual behavior in male Sprague Dawley rats. As well as fear the most effective plant parts have aphrodisiac activity. Thirty rats were divided into 5 groups (A-E) consisting of group A given 0.5% Na CMC colloid solution (normal control), group B given X-gra® suspension dosage 51.37 mg / kgBW (control positive), group C was given root ethanol extract dosage 200mg / kgBB, group D was given stem ethanol extract dosage 200mg / kgBB and group E was given leaf ethanol extract dosage 200mg / kgBB. The aphrodisiac test was observed on the 31st day with a ratio of male and female rats (1: 2). All parameters tested in the extract group showed significant differences with the normal group. This showed an aphrodisiac effect in all extract groups. The 200 mg / KgBB stem extract group reduced latent rates and intromission mounts as well as increased copulation rates, showing a marked increase in the number of intromissions, reduced ejaculatory latency and inter-intromission interval, and increased ejaculation frequency. which was not significant in the X-gra group (positive control) (p